Cover Image, Volume 36, Issue 3. (2nd February 2023) - Sharma, Gaurav; Maptue, Nesmine; Rahim, Mohsin; Trigo Mijes, Miriam L.; Hever, Thomas; Wen, Xiaodong; Funk, Alexander M.; Malloy, Craig R.; Young, Jamey D.; Khemtong, Chalermchai
Abstract : The cover image is based on the Research Article Oxidation of hyperpolarized [1‐ 13 C]pyruvate in isolated rat kidneys by Gaurav Sharma et al., https://doi.org/10.1002/nbm.4857 .